2021
DOI: 10.1038/s41598-020-80704-4
|View full text |Cite
|
Sign up to set email alerts
|

Elevated temperatures diminish the effects of a highly resistant rice variety on the brown planthopper

Abstract: This study compares the effects of temperature (constant at 15, 20, 25, 30 and 35 °C) on adult longevity, oviposition, and nymph development of the brown planthopper, Nilaparvata lugens, on susceptible and resistant rice varieties. The resistant variety contained the BPH32 gene. In our experiments, nymphs failed to develop to adults at 15, 20 and 35 °C on either variety. Host resistance had its greatest effect in reducing adult survival at 20–25 °C and its greatest effect in reducing nymph weight gain at 25 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
12
1
Order By: Relevance
“…Our experiments were conducted on relatively young plants because maximum egg laying by BPH and WBPH occurs in young plants [ 59 ] and egg parasitoids are most abundant at early crop stages [ 38 , 60 ]. We found no significant effect of variety on egg laying by either planthopper species, or by GLH ( Table S1 ); however, recent studies have shown that egg laying by BPH under no-choice conditions is heavily affected by the host of the female parent (i.e., TN1 in this study), with reductions in egg laying apparent as a lack of successive oviposition cycles [ 61 ]. The success of IR62 therefore relies on effective suppression, or losses in the reproductive potential of early generations of nymphs produced by immigrating females, which occurs during early crop stages.…”
Section: Discussioncontrasting
confidence: 52%
“…Our experiments were conducted on relatively young plants because maximum egg laying by BPH and WBPH occurs in young plants [ 59 ] and egg parasitoids are most abundant at early crop stages [ 38 , 60 ]. We found no significant effect of variety on egg laying by either planthopper species, or by GLH ( Table S1 ); however, recent studies have shown that egg laying by BPH under no-choice conditions is heavily affected by the host of the female parent (i.e., TN1 in this study), with reductions in egg laying apparent as a lack of successive oviposition cycles [ 61 ]. The success of IR62 therefore relies on effective suppression, or losses in the reproductive potential of early generations of nymphs produced by immigrating females, which occurs during early crop stages.…”
Section: Discussioncontrasting
confidence: 52%
“…b IR24 and NIL-BPH20. Means in each column followed by a different letter differ significantly (P < 0.05) high temperature (34-35°C, the prediction temperature of 2100) would greatly reduce N. lugens survival rate (Horgan et al 2020;Horgan et al 2021a;Horgan et al 2021b;Wang et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, several BPH resistance genes (BPH4, BPH9, BPH10, BPH18, BPH21, BPH21, BPH32, and BPH2 + 32) would lose their resistance due to climate change. In addition, another three BPH resistant varieties, IR26 (BPH1), IR36 (BPH2) and IR62 (BPH26 + 32), would lose the resistance under elevated temperature (Horgan et al 2021a;Wang et al 2010). These results imply that we need to use these insect-resistance traits/genes very carefully to prevent the development of a loss-of-function effect on the insect-resistant varieties in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The Ovipostion 20.2 ḟ/m test also indicated relatively low egg-laying on the same resistant plants. However, a recent, detailed study of oviposition in planthoppers indicates that much of the egg load of females is derived from the host on which the female develops, with subsequent egg-laying cycles determined by the food acquired during oviposition [ 57 ]. For example, in our oviposition test, the females were reared on TN1 before transfer to test lines and were therefore capable of laying large numbers of eggs during an initial oviposition cycle, even on the resistant varieties.…”
Section: Discussionmentioning
confidence: 99%